The Cys(3)-His(1) Motif of the Respiratory Syncytial Virus M2-1 Protein Is Essential for Protein Function - Hardy, Richard W. (American Society for Microbiology, 2000)
The M2 gene of respiratory syncytial (RS) virus has two open reading frames (ORFs). ORF1 encodes a 22-kDa protein termed M2-1. The M2-1 protein contains a Cys(3)-His(1) motif (C-X(7)-C-X(5)-C-X(3)-H) near the amino terminus. This motif is conserved in all human, bovine, and ovine strains of RS virus. A similar motif found in the mammalian transcription factor Nup475 has been shown to bind zinc. The M2-1 protein of human RS virus functions as a transcription factor which increases polymerase processivity, and it enhances readthrough of intergenic junctions during RS virus transcription, thereby acting as a transcription antiterminator. The M2-1 protein also interacts with the nucleocapsid protein. We examined the effects of mutations of cysteine and histidine residues predicted to coordinate zinc in the Cys(3)-His(1) motif on transcription antitermination and N protein binding. We found that mutating the predicted zinc-coordinating residues, the cysteine residues at amino acid positions 7 and 15 and the histidine residue at position 25, prevented M2-1 from enhancing transcriptional readthrough. In contrast, mutations of amino acids within this motif not predicted to coordinate zinc had no effect. Mutations of the predicted zinc-coordinating residues in the Cys(3)-His(1) motif also prevented M2-1 from interacting with the nucleocapsid protein. One mutation of a noncoordinating residue in the motif which did not affect readthrough during transcription, E10G, prevented interaction with the nucleocapsid protein. This suggests that M2-1 does not require interaction with the nucleocapsid protein in order to function during transcription. Analysis of the M2-1 protein in reducing sodium dodecyl sulfate-polyacrylamide gels revealed two major forms distinguished by their mobilities. The slower migrating form was shown to be phosphorylated, whereas the faster migrating form was not. Mutations in the Cys(3)-His(1) motif caused a change in distribution of the M2-1 protein from the slower to the faster migrating form. The data presented here show that the Cys(3)-His(1) motif of M2-1 is essential for maintaining the functional integrity of the protein.